A GENERALIZED GROBMAN-HARTMAN THEOREM - Bernardes Jr, Nilson C. (2020)
We prove that any generalized hyperbolic operator on any Banach space is structurally stable. As a consequence, we obtain a generalization of the classical Grobman-Hartman theorem.